ChemInform Abstract: Synthesis of Boron‐ and Silicon‐Containing Amino Acids Through Copper‐Catalyzed Conjugate Additions to Dehydroalanine Derivatives. Issue 36 (September 2015) - Bartoccini, Francesca; Bartolucci, Silvia; Lucarini, Simone; Piersanti, Giovanni
Abstract A regioselective hydroboration and hydrosilylation of dehydroalanines is presented.